2005
DOI: 10.1136/jech.2003.018085
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Antonovsky's sense of coherence scale: a systematic review

Abstract: Study objective: The aim of this paper is to systematically review and analyse the validity and reliability of Antonovsky's life orientation questionnaire/sense of coherence scale (SOC). Design: The study is descriptive and analytical with a systematic integration of the contemporary knowledge base on the salutogenic research published 1992-2003. The review includes 458 scientific publications and 13 doctoral theses. Setting: Worldwide, based on postgraduate scientific publications in eight authorised database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

109
1,213
11
62

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,253 publications
(1,395 citation statements)
references
References 101 publications
109
1,213
11
62
Order By: Relevance
“…The sense of coherence (SOC) mean score was 149.3 (SD = 13.9), which is similar to previous observations in this age group (Eriksson and Lindström, 2005).…”
Section: Individual Psychosocial Variablessupporting
confidence: 89%
“…The sense of coherence (SOC) mean score was 149.3 (SD = 13.9), which is similar to previous observations in this age group (Eriksson and Lindström, 2005).…”
Section: Individual Psychosocial Variablessupporting
confidence: 89%
“…It is made up of 11 items, and higher scores reflect higher perceived social support. The short version of the Sense of Coherence Scale (Lundberg and Peck 1995) based on Antonovsky's Sense of Coherence Scale contains three items corresponding to the dimensions of manageability, meaningfulness, and comprehensibility, which reflect a global orientation of viewing the world and the individual environment (Eriksson and Lindström 2005). The total scale score ranges from 0 to 6, such that the higher the value, the lower the sense of coherence.…”
Section: Methodsmentioning
confidence: 99%
“…Statements are rated on a scale from 1 to 7 and ratings are summed to give total scores ranging from 13 to 91, where higher scores indicate a stronger sense of coherence. The Swedish version of the SOC-13 has been used in several studies in patients with different diagnoses, alphas reported between 0.76 -0.87 (Eriksson & Lindström, 2005).…”
Section: Sense Of Coherence Scalementioning
confidence: 99%